Steady-state pharmacokinetics of lithium in healthy volunteers receiving concomitant meloxicam - Türck, D (Blackwell Science Inc, 2000)
AIMS: This open, controlled study investigated the effect of concomitant 15 mg oral meloxicam on the pharmacokinetics of lithium in healthy male volunteers. METHODS: On days 1–14 lithium was coadministered with meloxicam to 16 volunteers; on days 10–14 lithium was administered in individualized dosage regimes to achieve stable lithium plasma concentrations in the lower therapeutic range of 0.3–0.7 mmol l(−1). A 12 h steady-state concentration profile for lithium was obtained at day 14, after which meloxicam was withdrawn. The lithium dose remained unchanged from day 15 to day 22, at which time a second lithium concentration profile was determined. RESULTS: Lithium and meloxicam were well tolerated throughout the study and all 16 volunteers completed the study. Lithium predose concentrations (C(pre,ss)) and area under the curve (AUC(ss)) values both increased by 21% (paired t-test P = 0.0002; 90% confidence intervals for test/reference ratios: 113–130% and 115–128%, respectively) when lithium was coadministered with meloxicam compared with values obtained for lithium alone. The geometric mean lithium C(pre,ss) was 0.65 mmol l(−1) when coadministered with meloxicam and 0.54 mmol l(−1) for lithium alone. Lithium C(max,ss) values were increased by 16% by coadministration of meloxicam, from 0.97 mmol l(−1) to 1.12 mmol l(−1). The total plasma clearance of lithium was lower with concomitant meloxicam administration (82.5% of value for lithium alone). CONCLUSIONS: Meloxicam (15 mg) moderately increased the plasma concentration of lithium in healthy volunteers, but by a magnitude thought to be of low clinical relevance. Nevertheless, lithium plasma concentrations should be closely monitored in patients receiving concomitant meloxicam and lithium therapy.